Disonansi Naratif dalam Komunikasi Korporasi: (Studi Kasus Ketidaksesuaian Klaim Produk dan Realitas Teknis pada Brand Aqua) - Nadhif Akmaludin; Laili Zulfa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the narrative dissonance in the corporate communication of the Aqua brand, especially in the context of the crisis of meaning that arises between claims of natural purity and technical findings related to the use of borewells in the production process. Using a qualitative approach through content and narrative analysis, the study integrates two main theoretical frameworks: the Narrative Paradigm (Fisher, 1984) and Image Repair Theory (Benoit, 1995). The analysis focused on how companies are building, maintaining, and renegotiating their corporate narrative amid public pressure and consumer expectations. The results show that the legitimacy crisis arises due to the symbolic mismatch between the narrative of